(untitled) (Bangladesh Journal of Medicine, 2020)
In December 2019 an outbreak of viral pneumonia occurredinWuhan, Hubei Province of People’sRepublic of China (PRC). Later, it was found the responsible virus was SARS-CoV-2 and WHOrecognized it as a Pandemic on 11th March 2020. As of 15th July, in 213 countries, 580,038 deathshave occurred among 13,382,020 cases. Currently, many research are going on throughout theworld and they are coming up with new findings and observations every day. Based on the currentpublished literatures, this review systemically summarizes up to date information regarding structureof the causative agent, epidemiology, pathogenesis, clinical manifestations, diagnosis and treatmentoptions of COVID-19 in the hope that it will add to the knowledge of medical professionals andformulate better plans for future. Bangladesh J Medicine July 2020; 31(2) :81-93